PENGARUH KOMPETENSI PEGAWAI TERHADAP KUALITAS PELAYANAN DI KANTOR CAMAT SAJAD KABUPATEN SAMBAS - Yunni Hanitha E.42008009 (FISIP Universitas Tanjungpura Pontianak, 2012)
The title of this research is “The Effect of Employee’s Competency to Service Quality in Sajad district office, Sambas's Regency ”.This research is supposed to know and analyze how much employee’s competency gives effect to service quality in Sajad district office, Sambas regency. Quantitative approach was used in this research. The techniques were using quesioner, interview and documentation. From quesioner data was gotten and proceed by using product moment formula and simple regression SPSS 17 version was used to analyze. Population and sample were all 30 village instruments in Sajad district. The result shows there was significant effect from employee’s competency to service quality. From determinant coefficient counting, the effect of employee’s competence to service quality in Sajad district office, Sambas regency was 30,69% and the rest 69,31% was another factors which is not in this research. Key word: Employee’s Competency and Service quality